Virtual and Real: Ideas and Tools for an Enhanced Theatre in an Empathic Direction - Coco, Giorgia (Mimesis Journal, 2024)
Tracing the evolution of the term "virtual" in relation to the real, this article aims to valorize VR technology as a tool for enhancing theater in an empathic direction. By providing examples of performative outcomes in mixed VR/live formats, the article highlights experiments that utilize VR as a tool for fostering empathic engagement. A portion of the article focuses on the experimental project "Specimens/Exemplars," an unprecedented mixed performance piece (VR/live) with an original script written by the author, which also serves as a social experiment.